2018
DOI: 10.1097/psy.0000000000000505
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of the Effort-Reward Imbalance Model of Workplace Stress and Hypothalamic-Pituitary-Adrenal Axis Measures of Stress

Abstract: ERI and OC were similarly related with HPA responsivity. However, because OC moderated the relationship between ERI and HPA axis markers, the importance of OC should not be overlooked. Because OC is likely more malleable than ERI to intervention, this may be a promising avenue for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 38 publications
2
39
1
3
Order By: Relevance
“…Karlson et al (2012) commented that varying conditions of the workplace, type and duration of stress, and methodological factors may account for discordant findings. The meta-analysis by Eddy et al (2018) specifically reported a positive association between ERI and the following two indices of the HPA axis: the overall volume of cortisol released during the waking period, and the increase in cortisol from awakening to 30 min post-awakening (often referred to as CAR); a result not consistent with the current findings.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Karlson et al (2012) commented that varying conditions of the workplace, type and duration of stress, and methodological factors may account for discordant findings. The meta-analysis by Eddy et al (2018) specifically reported a positive association between ERI and the following two indices of the HPA axis: the overall volume of cortisol released during the waking period, and the increase in cortisol from awakening to 30 min post-awakening (often referred to as CAR); a result not consistent with the current findings.…”
Section: Discussioncontrasting
confidence: 89%
“…A meta-analysis of 62 studies concluded that job stress and general life stress were positively associated with changes in awakening cortisol measures (Chida and Steptoe 2009). A recent meta-analysis of 32 studies (Eddy et al 2018) that examined ERI in relation to various physiologic measures of the HPA axis reported an association between greater ERI and increased HPA axis activity.…”
Section: Eri and The Physiological Stress Responsementioning
confidence: 99%
“…As substantial gender differences were reported in associations of work stress with cortisol, any brief account of findings seems difficult. In an excellent recent systematic review and meta-analysis, Eddy et al [ 22 ] summarized the results of 14 studies testing associations of ERI with cortisol, as well as 10 including data on over-commitment [ 51 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. In either gender (but more pronounced among men), an increase in CAR or elevated ACC was associated with ERI in a majority of studies, but often bypassing statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Although we applied an established literature search strategy (see below), it does not represent a systematic review and meta-analysis. Rather, we draw major information from five recent systematic reviews [ 21 , 22 , 23 , 24 , 25 ], from a recent book chapter [ 26 ], and from an additional electronic search in the databases PubMed and PsycINFO. This literature search included the time period from 1 January 2011 until 31 August 2017 (by Jian Li).…”
Section: Methodsmentioning
confidence: 99%
“…Altered functioning of the hypothalamicpituitary-adrenal axis and increased endogenous inflammation were proposed as two promising markers of such pathways (8,9). In fact, for all three models of an adverse psychosocial work environment, associations with altered cortisol secretion and/or increased inflammation were demonstrated (47)(48)(49). These preliminary data support a mediating role of stress-biological mechanisms linking exposure to the development of depressive disorders, although longitudinal evidence on these pathways is still missing.…”
Section: Discussionmentioning
confidence: 95%